Quetiapine Modulates Histone Methylation Status in Oligodendroglia and Rescues Adolescent Behavioral Alterations of Socially Isolated Mice - Chen, Xianjun; Liu, Hao; Gan, Jingli; Wang, Xiaorui; Yu, Guangdan; Li, Tao; Liang, Xuejun; Yu, Bin; Xiao, Lan (Frontiers in Psychiatry, 2020)
Epigenetic alterations and impaired oligodendroglial myelination in the prefrontal cortex have been shown to correlate with behavioral and cognitive dysfunctions in social deprivation. Our previous study demonstrated that quetiapine, an atypical antipsychotic, could promote oligodendroglial differentiation and myelination. However, whether and how quetiapine could be beneficial in modulating aberrant epigenetic alterations in oligodendroglial cells and relieving behavioral alterations from social isolation is unknown. In this study, quetiapine was orally administered in adolescent mice undergoing mild stress of social isolation. We firstly confirmed that social isolation during a novel adolescent period could impair sociability, but not locomotive behaviors in mice. Moreover, quetiapine alleviated myelin deficits, and increased levels of histone methylation (H3K9me3) in mature oligodendroglia in the prefrontal cortex of socially isolated mice. Strikingly, quetiapine treatment significantly increased locomotive activity, and successfully reversed social avoidance behavior of the socially isolated mice. Taken together, our data suggest that quetiapine may rescue behavioral changes from social isolation through modulating epigenetic status towards the beneficial direction for oligodendroglial maturation, providing new insights into the pharmacological mechanism of quetiapine for mental illnesses.